2017
DOI: 10.18632/oncotarget.16515
|View full text |Cite
|
Sign up to set email alerts
|

Penfluridol suppresses glioblastoma tumor growth by Akt-mediated inhibition of GLI1

Abstract: Glioblastoma (GBM) is the most common brain tumor with poor survival rate. Our results show that penfluridol, an antipsychotic drug significantly reduced the survival of ten adult and pediatric glioblastoma cell lines with IC50 ranging 2–5 μM after 72 hours of treatment and induced apoptosis. Penfluridol treatment suppressed the phosphorylation of Akt at Ser473 and reduced the expression of GLI1, OCT4, Nanog and Sox2 in several glioblastoma cell lines in a concentration-dependent manner. Inhibiting Akt with LY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Previous studies have shown that penfluridol suppresses the growth of breast cancer, pancreatic cancer, and glioblastoma cells in vitro by various mechanisms [27][28][29]. In our study, we wanted to evaluate whether a low concentration of penfluridol affects the angiogenic potential of endothelial cells.…”
Section: Identification Of Non-toxic Penfluridol Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that penfluridol suppresses the growth of breast cancer, pancreatic cancer, and glioblastoma cells in vitro by various mechanisms [27][28][29]. In our study, we wanted to evaluate whether a low concentration of penfluridol affects the angiogenic potential of endothelial cells.…”
Section: Identification Of Non-toxic Penfluridol Concentrationsmentioning
confidence: 99%
“…Penfluridol is a potent, long-acting oral antipsychotic drug long used for schizophrenia, acute psychosis, and Tourette syndrome [23][24][25][26]. Our previous studies have shown the anti-cancer efficacy of penfluridol against breast, brain, and pancreatic carcinoma [27][28][29][30]. However, there is no study on the effect of penfluridol on the tumor vascular microenvironment, especially in clinically relevant doses prescribed for schizophrenia and other psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported that this compound reduces cancer growth in vitro and in vivo 915 . Encouraging tumorkilling data and ability of this drug to cross the blood-brain barrier (BBB) prompt the idea of using this agent in the treatment of glioblastoma 12,13 and cancers that have high rates of metastasis in the brain, including metastatic triple-negative breast cancer 10 and lung cancers 14 . However, in vivo data also indicated that anticancer dosage should be considerably higher (estimated at 50 mg of daily dosing in human) 1012,15,16 than those used for the treatment of chronic schizophrenia and similar psychotic disorders (weekly oral dosing of 20 mg to 100 mg, 160 mg for resistant cases) 17 .…”
mentioning
confidence: 99%
“…Encouraging tumorkilling data and ability of this drug to cross the blood-brain barrier (BBB) prompt the idea of using this agent in the treatment of glioblastoma 12,13 and cancers that have high rates of metastasis in the brain, including metastatic triple-negative breast cancer 10 and lung cancers 14 . However, in vivo data also indicated that anticancer dosage should be considerably higher (estimated at 50 mg of daily dosing in human) 1012,15,16 than those used for the treatment of chronic schizophrenia and similar psychotic disorders (weekly oral dosing of 20 mg to 100 mg, 160 mg for resistant cases) 17 . Earlier, clinical data report neurological side effects attributed to the antipsychotic use of penfluridol, including epilepsy, fatigue, dyskinesias, Parkinsonism, akathisia, dystonia and depression, although the numbers are at the lower range 1820 .…”
mentioning
confidence: 99%
See 1 more Smart Citation